Improving the properties of spring and springs steels by changing their structure - Namazov, S.N.; Gahramanov, V.F.; Rzayev, N.S.; M.A. Shahverdiyev; Hamdullayeva, I.H.; Azimova, Lala (My University, 2025)
A large number of various spring alloys are used in industry, since depending on the service conditions of the elastic elements, as well as their shape and size, they must differ in mechanical, physicochemical and technological properties. Therefore, spring alloys have different chemical composition and structure and are subjected to various types of heat treatment. Classification of spring alloys can be carried out according to a number of features. Firstly, alloys can be divided by the main methods of strengthening. Steels and alloys, strengthened by cold plastic deformation and subsequent lowtemperature heating (tempering or annealing). This group includes steels with an increased carbon content (0.4-1.3%), subjected to strengthening by cold plastic deformation (after preliminary heat treatment), and after cold working - low tempering. In this case, preliminary heat treatment makes a certain, and in some cases, a very significant contribution to the overall strengthening. Depending on the structure obtained during heat treatment, the absolute degree of strengthening in the process of cold plastic deformation also changes. During the cold working process, the phase state of the steel remains practically unchanged, but only the fine structure changes due to an increase in the dislocation density. As a result of additional tempering (aging), residual stresses are removed, dislocations are redistributed, segregations are formed on them, which causes a strong increase in the elastic limit, relaxation resistance and other properties of the steel.
Keywords: Steel; Nickel; Plastic; Deformation